Workspace preferences and non-preferences in Activity-based Flexible Offices: Two case studies. (February 2020) - Babapour Chafi, Maral; Harder, Mette; Bodin Danielsson, Christina
Abstract: Activity-based Flexible Offices (AFOs) are innovations in workspace design that are being increasingly implemented in organisations. While most studies investigate satisfaction and perceived work support in AFOs, employees' workspace preferences are not addressed in the literature. The aims of this study were to (i) identify workspace preferences and non-preferences in AFOs, and (ii) investigate whether employees' workstation choices support their activities and align with their preferences. Two Swedish municipalities participated in the study. Data collection involved 27 semi-structured interviews and annotations on architectural drawings. The results showed that the interviewees preferred workstations that were both desirable and functional, and avoided workstations that were undesirable. This was due to functional, social, emotional and symbolic aspects of the workspaces as well as their physical structure and stimuli. The approach used in this paper can be adopted for improving the design of AFOs, thereby mitigating the stress of finding a suitable workstation. Highlights: Investigation of usage preferences underlined competition for desirable workspaces. Preferences were based e.g. on functional, social, emotional and symbolic aspects. Undesirable workspaces were avoided, despite their usefulness. Non-preferences were due to deficient workspaces and mixing of workspaces. Replacing undesirable spaces may mitigate the stress of finding suitable spaces.